Obstacles of professional behavior among medical trainees: A qualitative study from Iran (2018) - Neda Yavari; Fariba Asghari; Zahra Shahvari; Saharnaz Nedjat; Bagher Larijani (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Despite all efforts that have been made to promote professional behavior among medical trainees, unfortunately, reports from medical schools around the world confirm the prevalence of nonprofessional behaviors by medical students. Experts in the field of medical ethics and medical education in different countries have suggested several reasons for failing to minimize unprofessional performance among medical students. MATERIALS AND METHODS: This qualitative study aimed to promote our understanding from the challenges faced by Iranian medical students in providing professional behavior. The study was first conducted in the form of a semi-structured face-to-face interview with medical students and then completed with a focus group discussion (FGD) session. Forty-nine medical students participated in the interviews and 11 students participated in the FGD session. Qualitative conventional content analysis was used for examining the data. RESULTS: The participants classified the obstacles of professional behavior into the following three main categories: problems related to educational system, problems related to the society, and problems related to students themselves. CONCLUSION: Regarding the impact of various personal, social, and educational factors on the creation and expansion of unprofessional behaviors among medical students, it is essential to have a comprehensive approach for solving the problem.